2020
DOI: 10.1007/s11433-019-1495-3
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional high temperature superconductivity in cubic zinc-blende transition metal compounds

Abstract: We consider possible high temperature superconductivity (high-Tc) in transition metal compounds with a cubic zinc-blende lattice structure. When the electron filling configuration in the d-shell is close to d 7 , all three t2g orbitals are near half filling with strong nearest neighbor antiferromagnetic (AFM) superexchange interactions. We argue that upon doping, this electronic environment can be one of "genes" to host unconventional high Tc with a time reversal symmetry broken d 2z 2 −x 2 −y 2 ± id x 2 −y 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The discoveries of superconductivity (SC) in the complex copper oxide [1] and the iron-based pnictide [2] stimulate enthusiasm to search for SC especially in late 3d-transition-metal (Fe, Co, Ni, and Cu) compounds [3][4][5][6][7]. Among them, the Co-based superconductors are very limited so far.…”
Section: Introductionmentioning
confidence: 99%
“…The discoveries of superconductivity (SC) in the complex copper oxide [1] and the iron-based pnictide [2] stimulate enthusiasm to search for SC especially in late 3d-transition-metal (Fe, Co, Ni, and Cu) compounds [3][4][5][6][7]. Among them, the Co-based superconductors are very limited so far.…”
Section: Introductionmentioning
confidence: 99%
“…ScN, TiN, VN and CrN); in recent years, late TMNs, in particular cobalt mononitride (CoN) has emerged as a interesting material for application as a high capacity anode for Li-ion batteries [13,14,15,16], as a highly efficient and low-cost electrocatalyst for HER and OER [17,18,10], non aqueous supercapacitor [19] and electrode with similar characteristic as that of Pt for mesoscopic solar cells [20]. Recently, superconductivity has also been predicted in zinc blende (ZB)-type CoN [21,22]. However, unlike other TMNs, CoN is not explored much and the relevant interest and potential of this for application in renewable energy sector requires a deeper understanding of the structural and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent experiments 11,12 reported that in one kind of cuprates with a large amount of oxygen vacancies, Ba 2 CuO 3+δ with 0 ≤ δ ≤ 1, high-T C superconductivity is still observed. Various theoretical works 11,[13][14][15][16][17][18] focusing on Ba 2 CuO 3+δ have been proposed to determine the pairing symmetry and low-temperature phases in different crystal structures. Liu 19 and coworkers showed by first principle calculation that Ba 2 CuO 3+δ can be viewed as doped Ba 2 CuO 3 , which exhibits a CuO chain structure shown in Fig.…”
Section: Introductionmentioning
confidence: 99%